2010
DOI: 10.1590/s1678-91992010000300016
|View full text |Cite
|
Sign up to set email alerts
|

Purification and biological effects of a C-type lectin isolated from Bothrops moojeni

Abstract: Snake venom proteins from the C-type lectin family have very distinct biological activities despite their highly conserved primary structure, which is homologous to the carbohydrate recognition region of true C-type lectins. We purified a lectin-like protein (BmLec) from Bothrops moojeni venom and investigated its effect on platelet aggregation, insulin secretion, antibacterial activity, and isolated kidney cells. The BmLec was purified using two chromatographic steps: affinity chromatography and reverse phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 31 publications
0
13
0
4
Order By: Relevance
“…Glycoconjugates present on bacterial cell surfaces, such as peptidoglycans, lipopolysaccharides and teichoic acids, constitute potential lectin targets (Lee et al, 1998;Santi-Gadelha et al, 2006). Recently, it was reported that snake venom lectins are able to inhibit growth of phytopathogenic bacteria (Rádis-Baptista et al, 2006;Barbosa et al, 2010); however, the interactions between snake venom lectins and human pathogenic bacteria have not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Glycoconjugates present on bacterial cell surfaces, such as peptidoglycans, lipopolysaccharides and teichoic acids, constitute potential lectin targets (Lee et al, 1998;Santi-Gadelha et al, 2006). Recently, it was reported that snake venom lectins are able to inhibit growth of phytopathogenic bacteria (Rádis-Baptista et al, 2006;Barbosa et al, 2010); however, the interactions between snake venom lectins and human pathogenic bacteria have not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Barbosa et al (2010) reported the in vitro antibacterial and antiplatelet aggregation activities, the insulin secretion stimulation, and the in vivo improvement of kidney function for a lectin-like protein isolated from BMV. Morais et al (2012) showed the anticoagulant and fibrinogenolytic activities of moojenin, a metalloproteinase extracted from BMV.…”
Section: Discussionmentioning
confidence: 99%
“…All SVgalLs are homodimeric proteins composed of disulfide-linked monomers presenting molecular mass varying from 14 to 16.2 kDa. The primary structures of 12 SVgalLs were determined, and presented from 134 to 136 amino acid residues as described for the following lectins: RSL—rattlesnake lectin from Crotalus atrox [ 23 ], ApL— Agkistrodon piscivorus piscivorus lectin [ 15 ], BaL— Bitis arietans lectin [ 13 ], CrL— Crotalus ruber lectin [ 18 ], BiL— Bothrops insularis lectin [ 16 ], BmLec— Bothrops moojeni lectin [ 24 ], BpalL— Bothrops pauloensis lectin [ 21 ], BJcuL— Bothrops jararacussu lectin [ 25 ], BpirL— Bothrops pirajai lectin [ 17 ], LmL— Lachesis muta stenophrys lectin [ 26 ], ToL— Trimeresurus okinavensis lectin [ 27 ] and TsL— Trimeresurus stejnegeri lectin [ 28 ]. Amino acid sequence analysis among the referenced SVgalLs using BLAST searching tool [ 29 ] showed an identity degree from 82 to 97 % among them, indicating a high primary structural similarity within these lectins.…”
Section: Reviewmentioning
confidence: 99%
“…Carbohydrate recognition domain (CRD) is indicated by the blue box. Primary structure according to lectins: RSL [GI: 126130], ApL [GI: 510120659], BaL [GI: 34922645], CrL [GI: 118572769], BiL [GI: 82126834], BmLec [ 24 ], BpalL [GI: 527504051], BJcuL [ 25 ], BpirL [GI: 510120660], LmL [GI: 1881829], ToL [ 27 ] and TsL [GI: 7674107] …”
Section: Reviewmentioning
confidence: 99%